Inhalation Devices: Various forms of administration for Therapeutic Optimization - Renata Cristina de Angelo Calsaverini Leal (Open Journal of Asthma - Peertechz Publications, 2017)
Introduction: Aerosol therapy consists of spraying liquid particles suspended for therapeutic purposes in the respiratory tract. With direct absorption and deposition at the lung level, avoiding side effects and presenting fast response time. Several factors influence the drug action, such as size, particle movement, ventilatory fl ow, pulmonary expansion, anatomy, respiratory mechanics and the nebulizer and patient interface. The therapeutic optimization depends on the type of nebulizer differentiating itself by the physical principle that generates the mist. Objectives: Check advantages and disadvantages of different inhalation devices. Methodology. This is a review of the PubMed database using descriptors: ultrasonic and jet nebulizer, aerosol deposition in the lung, metered dose inhaler and dry, inhaler therapy. Results: Different devices are mentioned in the literature: pneumatic and ultrasonic nebulizers (administering solutions), metered pressurized inhalers - pMDI used with or without expander chamber (administering suspensions) and dry powder inhalers - DPI (administering powder). Discussion and Conclusion: The US has advantages: quiet, does not require coordinating abilities, without propellant gases and quick nebulization with small amount of solution. Disadvantages: change in the active principle of thermosensitive drugs, deposition in the oropharynx and VAI of 2% of inhaled particles. The NJ has 10% VAI drug deposition. Disadvantages: longer use time, need energy source, hinders molecular transport and has variable fl ow rate. DPI has advantages: portable, simple, activated by inspiration and the dose deposited varies from 15 to 40%. Disadvantage: requires respiratory coordination.The pMDI offers advantages: deposition in VAI of 37%, practical, allows a micropulverization.  Disadvantages:Required high inspiratory fl ow. Aerosol therapy aims at deposition of particles with a diameter of less than 5 μm in VAI. To achieve a concentration similar to the inhaled route in VA tissues, a higher dose of oral medication is required. For each patient there is a suitable inhaler.